A Laboratory Study Comparing the Effectiveness of Verbal and Nonverbal Rapport-Building Techniques in Interviews. Issue 5 (3rd September 2021) - Novotny, Eric; Frank, Mark G.; Grizzard, Matthew
ABSTRACT: The relative and combined effectiveness of verbal versus nonverbal techniques in eliciting rapport during interviews is unknown. The effectiveness of one verbal and one nonverbal behavioral technique presumed to be associated with rapport-building were compared to determine if either or both could influence participants to disclose more personal information. In an experiment, an interviewer performed one of four conditions with participants: verbal commonalities, mirrored body postures, a combination of both, or neither (control). Results indicated that participants were more willing to discuss personal, or "closed" topics when verbal commonalities were used alone, versus in conjunction with nonverbal mirroring. The simple effect of mirroring trended in the predicted direction but was not significantly different from the control group. Practical and research-based implications for rapport-building in interviews are discussed.